Epidemiological analysis of the Kaohsiung city strategy for dengue fever quarantine and epidemic prevention - Pan, Chao-Ying; Liu, Wei-Liang; Su, Matthew-P.; Chang, Te-Pin; Ho, Hui-Pin; Shu, Pei-Yun; Huang, Joh-Jong; Lin, Li-Jen; Chen, Chun-Hong (BMC infectious diseases, 2020)
Dengue is endemic in over 100 countries and is an important public health problem worldwide. Dengue fever is not endemic in Taiwan; the importation of dengue viruses from neighboring countries via close commercial links and air travel is considered to be the cause of local outbreaks. Therefore, efforts toward disease control have focused on preventing the importation of dengue into Taiwan. In this study, we investigated the relationships between the numbers of imported and indigenous dengue cases to test the validity of this strategy. Data on cases of dengue fever that occurred between 2013 and 2018 were obtained from the surveillance systems of the Taiwan Center for Disease Control and Kaohsiung City Health Department. Standard epidemiological data, including the monthly numbers of indigenous and imported cases of dengue, were calculated. Potential associations between the numbers of indigenous and imported cases were investigated using correlation analyses. We identified a possible relationship between the period of disease concealment and the number of imported dengue cases, which resulted in epidemics of indigenous dengue fever within local communities. Further analysis of confirmed cases during previous epidemics in Kaohsiung City found that the risk of indigenous dengue fever may be related to the likelihood that patients with imported dengue fever will stay within local communities. Given the correlations found between imported and indigenous cases of dengue fever, as well as the relationship between the disease concealment period and the risk of indigenous dengue fever, prevention of disease importation and efficient identification of dengue cases within high-risk communities remain the major priorities for disease control.